Aruga laban sa droga redefining recovery for substance abuse victims among street children through child-friendly drug treatment and rehabilitation center - Ofalsa, Rennilyn Joy A.
Substance abuse is a growing problem in the Philippines that has affected many teenagers, and adults, including their families. In 2019, an estimated 1.7 million Filipinos were using dangerous drugs; however, only 5,277 were the recorded admissions in inpatient and outpatient facilities due to limited rehabilitation facilities (World Health Organization, 2021). In 2021, there are a total of 63 treatment and rehabilitation facilities, wherein 58 are residential and 5 are outpatient (Dangerous Drugs Board, 2021). Despite the already limited facilities, most of these are only geared towards teenagers and adults, but substance abuse is not limited to teenagers and adults only. Many street children in Manila are known to abuse toluene-based solvents, more commonly known as rugby. According to a report by Department of Social Welfare and Development (2003), the number of street children in the country increase by 6,365 annually, and half of them have at least once inhaled toluene-based solvents and other inhalants due to its accessibility and low cost. They resort to this act to alleviate their hunger and relieve their problems. Despite the growing problem, there is scant literature on the architectural programming of facilities that focus on treating addiction in children. This research will examine how to incorporate child-friendly spaces in the architectural design of a drug rehabilitation center for minors.